SUN-311 Adrenal Reserve Testing with the Glucagon Stimulation Test (GST) and Cosyntropin Stimulation Test (CST) in Deployed Veterans with Mild Traumatic Brain Injury - Nagireddi, Rama Priyanka; Win, Htet Htet; Wagstaff, Sarah; Neal, Moira; Friedman, Kathryn; Anderson, Robert J (Journal of the Endocrine Society, 2020)
Introduction: Mild Traumatic Brain Injury (mTBI) is associated with anterior pituitary hormone dysfunction. The potential long-term effect of this injury on pituitary function in Veterans is not clear. We reviewed the utility of the fixed dose Glucagon Stimulation Test (GST) compared with the high dose Cosyntropin Stimulation test (CST) for hypothalamic-pituitary-adrenal (HPA) reserve over time in these patients with mTBI. Methods: We present an interim report of our 4-year longitudinal prospective pilot study of pituitary function in Veterans diagnosed with mTBI. Of the 34 mTBI Veterans enrolled, we have tested 28 of them (4 female, 24 male; age and BMI, 31.5±7.0 years and 30.4±6.2, mean±SD, respectively) for baseline pituitary hormone levels and cortisol response to the CST. In 22 subjects growth hormone and cortisol responses to GST were tested at baseline (Year 0). Follow-up testing was done for 18 mTBI subjects in Year 1, 13 subjects in Year 2, 10 subjects in Year 3 and 5 subjects in Year 4. The same baseline data were obtained for 14 age-, sex-, deployment- and BMI-matched control subjects without mTBI (2 female,12 male; age and BMI 34.4±6.8 years and 30.5±4.9, mean±SD, respectively). Cortisol cutoffs of <18 mcg/dL with the CST and <9.0 mcg/dL with the GST were used for the diagnosis of adrenal insufficiency. Results: Secondary adrenal insufficiency (AI), likely partial, was identified during this study on 6 occasions: 3/22 subjects at Year 0, 1/18 at Year 1, 0/13 at Year 2, 1/10 at Year 3 and 1/5 at Year 4. Two baseline subjects with AI reverted to normal in Years 1-3, one relapsed in Year 4 and a third had no further testing. Correlations of the cortisol levels from GST vs the 60-minute cortisol from CST were significant at Year 0 (n=22, r=0.553, p=0.008) and at Year 1 (n=18, r=0.802, p<0.0001). Due to decreased numbers, there were no significant correlations at Years 2 through 4. Similar correlations were obtained using the 30-minute CST values. However, the CST cortisol value predicted the low GST value in only 2/6 subjects. The mean GST cortisol levels and 60-minute CST cortisol levels for subjects at each year were not significantly different over Years 0 through 4 based on ANOVA analyses (CST: F=1.519, p= 0.206; GST: F= 0.796, p=0.532). Conclusions: Secondary adrenal insufficiency, likely partial, related to mTBI was detected by GST on 6 occasions (twice in one patient) over 4 years of observation. GST can provide useful information about HPA axis reserve, and appears to be more reliable than CST. Identification of potential secondary adrenal insufficiency using the GST in Veterans with mTBI can provide a beneficial combined test for these patients when other testing is not feasible.